Akademi Pengajian Bahasa (APB) academic tour 2016 - Abang Madaud, Abang Fhaeizdhyall (Universiti Teknologi MARA, Sarawak, 2016)
The purpose of the visit was to inform the APB lecturers on the current development and issues at APB. Among the topics presented by the Dean and the Deputy Dean were transformation of the university and APB, new curriculum changes for English subjects and Jabatan Bahasa Arab dan Eropah (JBAE), recent developments in ATP, OPAL and scholarships, the focus on teaching, learning and community service, the language testing projects by the academy such as English Exit Test (EET), English Placement Test (EPT) and English Language Enhancement Program (ELEP), the use of dictionary in final examinations for ELC codes and Computer Based Testing (CBT) for ELC120 and ELC150. Simultaneously, the degree students were briefed on the English Exit Test (EET) at Dewan Jubli by Associate Professor Dr. Noraida.